N6-Methyladenosine Regulator-Mediated Immue Patterns and Tumor Microenvironment Infiltration Characterization in Glioblastoma - Xiong, Wu; Li, Cong; Wan, Bowen; Zheng, Ziyang; Zhang, Yingfei; Wang, Siming; Fan, Jin (Frontiers in Immunology, 2022)
Background: Epigenetic modifications, according to emerging evidence, perform a critical role for cellular immune response and tumorigenesis. Nonetheless, the role of N6-methyladenosine modification in shaping of the glioblastoma tumor microenvironment is unknown. Methods: N6-methyladenosine(m6A) methylation patterns in GBM patients were evaluated via multiple omics analysis of 15 m6A regulators and systematically correlated with tumor immune features. For quantification of N6-methyladenosine methylation patterns of individual patients,GM-score was developed and correlated with clinical and immunological characteristics. Results: Glioblastoma has two different m6A methylation patterns that are strongly associated with TME characteristics, tumor subtype, immunotherapy response, and patient prognosis. High-GM-score is associated with an immune tolerance phenotype dominated by the IDH1 wild molecular subtype and the Mesenchymal tissue subtype, as well as a high infiltration of immune cells and stromal cells and a poor prognosis. Furthermore, despite higher immune checkpoint expression, individuals with a high-GM-score have a poorer response to anti-CTLA4 immunotherapy regimens due to T-cells dysfunctional . Low-GM-score individuals had an immunodeficient phenotype dominated by IDH mutant molecular subtypes and Proneural tissue subtypes, with less immune cell infiltration and a better prognosis. Furthermore, patients with low-GM-scores had higher microsatellite instability (MSI) and t-cell exclusion scores, as well as a better response to anti-CTLA4 immunotherapy regimens. Conclusion: This study demonstrated that m6A modification patterns play an important role in the shaping of TME complexity and diversity. The GM-score could identify m6A modification patterns in individual patients, resulting in a more personalisation and efficacious anti-tumor immunotherapy strategy.